Electronic structure and magneto-optical Kerr spectra of an epitaxial Ni54.3Mn31.9Sn13.8 Heusler alloy film. (6th June 2017) - Uba, L; Bonda, A; Uba, S; Bekenov, L V; Antonov, V N
Abstract: In this joint experimental and ab initio study, we investigated the influence of chemical composition and martensitic phase transition on the electronic, magnetic, optical and magneto-optical properties of ferromagnetic shape-memory Ni–Mn–Sn alloys. Optical properties and polar magneto-optical Kerr effect (MOKE) spectra for Ni–Mn–Sn alloy film of composition Ni54.3 Mn31.9 Sn13.8 deposited epitaxially on MgO(0 0 1) substrate were measured over the photon energy range 0.8 ⩽ h ν ⩽ 5.8 eV, and the complete set of optical conductivity tensor elements were determined. To explain the microscopic origin of the optical and magneto-optical spectra, extensive first-principles calculations were made, using the spin-polarized fully relativistic linear-muffin-tin-orbital method. The electronic, magnetic and magneto-optical properties of Ni–Mn–Sn Heusler alloys were investigated for the cubic austenitic and 4O orthorhombic martensitic phases, in stoichiometric and off-stoichiometric compositions. The MOKE properties of Ni–Mn–Sn systems are very sensitive to deviation from stoichiometry. It was shown that the ab initio calculations reproduce experimental spectra well, and help to explain the microscopic origin of Ni–Mn–Sn optical and magneto-optical responses. The interband transitions responsible for the prominent structures in the Ni–Mn–Sn MOKE spectra have been identified—they come from relatively narrow energy intervals at several well-defined vicinities of high-symmetry directions of the Brillouin zone. Significant modification of the MOKE spectra can be considered as a fingerprint of martensitic phase transition in Ni–Mn–Sn alloys.